2022
DOI: 10.3390/ijms23126494
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Lipidomic and Transcriptomic Analysis Reveals Phospholipid Changes in Somatic Embryos of Picea asperata in Response to Partial Desiccation

Abstract: Partial desiccation treatment (PDT) is an effective technology for promoting the germination and conversion of conifer somatic embryos (SEs). PDT, as a drought stress, induces intensive physiological responses in phospholipid metabolism, which are not well understood in the conifer SEs. Here, we integrated lipidomics, transcriptomics and proteomics analyses to reveal the molecular basis of lipid remodeling under PDT in Picea asperata SEs. Among the 82 lipid molecular species determined by mass spectrometry, ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The maintenance of cell membrane stability and integrity is critical for controlling regular cell metabolism and physiological processes ( Ling et al., 2022 ). Glycerophospholipid is an important component of the cell membrane ( Calzada et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maintenance of cell membrane stability and integrity is critical for controlling regular cell metabolism and physiological processes ( Ling et al., 2022 ). Glycerophospholipid is an important component of the cell membrane ( Calzada et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Relatively few investigations have attempted to characterize the role of ABA-mediated glycerophospholipid metabolism in seed germination so far. However, most studies have focused on the involvement of phosphatidic acids in ABA signal pathways, influencing the germination process ( Zhang et al., 2004 ; Ling et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown the importance of lipid content in SE in Cichorium sp. and Picea asperata [61,62], and in tamarillo somatic embryos [18], which could explain the importance of choline in the overall variance of the data.…”
Section: Chemometric Analysismentioning
confidence: 99%
“…The maintenance of cell membrane stability and integrity is critical for controlling regular cell metabolism and physiological processes (Ling et al, 2022). Glycerophospholipid is an important component of the cell membrane (Calzada et al, 2016).…”
Section: 2mentioning
confidence: 99%
“…Relatively few investigations have attempted to characterize the role of ABA-mediated glycerophospholipid metabolism in seed germination so far. However, most studies have focused on the involvement of phosphatidic acids in ABA signal pathways, influencing the germination process (Zhang et al, 2004;Ling et al, 2022).…”
Section: 2mentioning
confidence: 99%